Effectiveness of Education on the Success of Early Breastfeeding Initiation in Women Giving Birth by CS - Winda Mutiasyah; Ita Herawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Knowing the effectiveness of education on the success of Early Breastfeeding Initiation in maternity mothers with SC. Quasi-experimental design with nonequivalent control group design. The sample in this study was all maternity mothers with SC at YPK Mandiri Hospital in November 2022 were 40 people. Sampling technique, namely accidental sampling. Only a small percentage of control group respondents succeeded in carrying out Early Breastfeeding Initiation, namely 2 people (10 %). Most of the respondents to the intervention group successfully carried out Early Breastfeeding Initiation, namely 18 people (90 %). Education is effective to increase the success of Early Breastfeeding Initiation (Asymp. Sig. (2-tailed) 0.000). Education is effective to increase the success of Early Breastfeeding Initiation. It is hoped that midwives can provide education about Early Breastfeeding Initiation to mothers during pregnancy checkups.